2015
DOI: 10.1016/j.icarus.2014.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of Uranus’ cloud scattering properties from IRTF/SpeX observations using a self-consistent scattering cloud retrieval scheme

Abstract: a b s t r a c tWe have developed a new retrieval approach to modelling near-infrared spectra of Uranus that represents a significant improvement over previous modelling methods. We reanalysed IRTF/SpeX observations of Uranus observed in 2009 covering the wavelength range 0.8-1.8 lm and reported by Tice et al. (Tice, D.S., Irwin,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 36 publications
4
62
2
Order By: Relevance
“…number density x extinction cross-section, per bar) for a cloud of particles with a single scattering albedo of and normalized phase function of 1.0. For a cloud located at several few bars, reasonable values based on the literature (Tice et al, 2013;Irwin et al, 2015), as discussed in Section 5.2, would suggest single scattering albedo of ~0.7 and a normalized phase function of ~ 0.4, yielding an optical depth ~3x our reported ' s bar -1 . Figure 6.…”
Section: Aerosols Scattering and Reflectancesupporting
confidence: 72%
See 3 more Smart Citations
“…number density x extinction cross-section, per bar) for a cloud of particles with a single scattering albedo of and normalized phase function of 1.0. For a cloud located at several few bars, reasonable values based on the literature (Tice et al, 2013;Irwin et al, 2015), as discussed in Section 5.2, would suggest single scattering albedo of ~0.7 and a normalized phase function of ~ 0.4, yielding an optical depth ~3x our reported ' s bar -1 . Figure 6.…”
Section: Aerosols Scattering and Reflectancesupporting
confidence: 72%
“…Particles much smaller than this produced less scattering at longer wavelengths and yielded marginally larger residuals; however, the errors in the K-band are large and the constraints are weak given that very little of the reflectance in the H-band originates from the same aerosols probed in the K-band. By including shorter wavelength observations, Irwin et al (2015) had found the scattering cross-sections of aerosols at these heights diminished more strongly in wavelength, consistent with mean particle sizes of only 0.1µm. As Fig.16 shows, using a refractive index suggested by Irwin et al (2015) for the tropospheric cloud, the wavelength dependence across the K-band alone is similar in shape for both particle sizes, with a magnitude that may be shifted based on other factors folded into the effective scattering optical depth; with the H-band dominated by scattering from different depths, our solutions are degenerate among different combinations of scattering parameters.…”
Section: Mean Retrieved Aerosol Profilesmentioning
confidence: 65%
See 2 more Smart Citations
“…Our cloud model is linked with a physical model that calculates cloud density and particle size. As presented in the literature, this is likely to bring a correlation between the VMR of methane and the cloud position (Irwin et al 2015;Lupu et al 2016). However, there might be cases in which this correlation is not significant as highlighted by Hu (2019), it depends on a combination of S/N, spectral resolution, and particular combinations of cloud position and methane VMR.…”
Section: Discussionmentioning
confidence: 88%